National dementia supporter programme in Japan. (July 2021) - Aihara, Yoko; Maeda, Kiyoshi
Due to the growing number of people with dementia worldwide, the role of dementia supporters is becoming increasingly important. In 2005, a national campaign called the Dementia Supporter Caravan was launched in Japan. However, the impact these trainings have on facilitating the work of dementia supporters is not quite understood. This study aimed to assess the challenges faced by dementia supporters in conducting activities for people with dementia. Our results showed that even after a period of six months since the training session, only half of the supporters had commenced new support activities. Future studies should examine the impact activities conducted by dementia supporters have on people with dementia and their family caregivers.